Photocatalysis for organic wastewater treatment: from the basis to current challenges for society - Sinar Mashuri, Salma Izati; Ibrahim, Mohd Lokman; Kasim, Muhd Firdaus; Mastuli, Mohd Sufri; Rashid, Umer; Abdullah, Abdul Halim; Islam, Aminul; Mijan, Nurul Asikin; Yie, Hua Tan; Mansir, Nasar; Mohd Kaus, Noor Haida; Yap, Taufiq Yun Hin (MDPI, 2020)
Organic pollutants such as dyes, antibiotics, analgesics, herbicides, pesticides, and stimulants become major sources of water pollution. Several treatments such as absorptions, coagulation, filtration, and oxidations were introduced and experimentally carried out to overcome these problems. Nowadays, an advanced technique by photocatalytic degradation attracts the attention of most researchers due to its interesting and promising mechanism that allows spontaneous and non-spontaneous reactions as they utilized light energy to initiate the reaction. However, only a few numbers of photocatalysts reported were able to completely degrade organic pollutants. In the past decade, the number of preparation techniques of photocatalyst such as doping, morphology manipulation, metal loading, and coupling heterojunction were studied and tested. Thus, in this paper, we reviewed details on the fundamentals, common photocatalyst preparation for coupling heterojunction, morphological effect, and photocatalyst’s characterization techniques. The important variables such as catalyst dosage, pH, and initial concentration of sample pollution, irradiation time by light, temperature system, durability, and stability of the catalyst that potentially affect the efficiency of the process were also discussed. Overall, this paper offers an in-depth perspective of photocatalytic degradation of sample pollutions and its future direction.